Jews and Christians exploring the past, present and future - Charlesworth, James H.; Blisard, Frank X.; Siker, Jeffrey S. (New York, NY Crossroad, 1990)
Includes bibliographial references and indexes.
Keywords: Judaism -- relations -- Christianity -- Congresses; Christianity and other religions -- Judaism -- Congresses; Judaism (Christian theology) -- history of doctrines -- Congresses